Peningkatan Pelayanan bagi Pegawai Glamping Kema Merbabu melalui Pelatihan Penampilan Diri - Imanina, Almas Nabili; Paninggiran, Herman Novry Kristiansen; Jannah, Desika Nur; Anggraini, Naila Putri; Lestari, Niken Savitri Oktariani (Jurnal Abdimas Pariwisata, 2024)
Improving Services for Glamping Kema Merbabu employees through Personal Appearance Training This community service is the result of collaboration with Glamping Kema Merbabu, Boyolali Regency as a participant. Glamping is a type of accommodation that is currently popular among tourists because it presents a camping-themed accommodation concept but the facilities offered are complete, similar to conventional hotels in general. The majority of employees who work at Kema Merbabu come from the local community, so the main focus of the activity is understanding the importance of personal appearance from the tips of the signs to the toenails, maintaining voice intonation and body movements, to how to deal with complaints from guests. Identify the main problems related to the lack of training and character development of Kema Merbabu. To overcome this, this training implements a solution in the form of a personal grooming program which includes training in interpersonal skills, work ethics and manners. This method involves direct lectures, personal guidance, social interaction and role play so that it is hoped that in the future it can have a positive impact on the personal and professionalism of all Kema Merbabu employees, as well as improving the image and quality of Kema Merbabu Glamping services.